TIPE RAGAM BAHASA PADA UJARAN DALAM NASKAH FILM â€œRAYA AND THE LAST DRAGONâ€ - Haq, Disa Khairina; Fitriani, Nurul (Universitas Majalengka, 2023)
The aim of this study is to identify and describe types of language style found in utterances used by the main character and other characters in â€œRaya and the Last Dragonâ€ movie script. It used qualitative approach with descriptive qualitative method in order to explain comprehensively and completely of the data finding. The result of the study showed that the characters in â€œRaya and the Last Dragonâ€ movie script use different language style depending on the situational context of where the conversation happened, and also depending on their interlocutors. Types of language style found in this study are frozen, consultative, casual, and intimate style.Key words:Â language style, type, utterances, movie script, characters.